Development And Evaluation of A Polyherbal Gel For Anti-Inflammatory Activity - Singh Rajput, Hakim; Singh, Sunder; Kumar Yadav, Vimal (Journal of Neonatal Surgery, 2025)
This study evaluates the physicochemical characteristics, phytochemical composition, and pharmacological potential of botanical extracts and gel formulations. The analysis of ash values, swelling indices, and solubility profiles provides insights into the purity and mineral content of turmeric rhizomes, rosemary leaves, borage seeds, Devil's roots, and Evening Primrose seeds. Phytochemical screening reveals diverse bioactive compounds, including flavonoids, anthocyanins, and polyphenols, contributing to their medicinal significance. The formulated gels exhibit optimal pH (6.1–6.3), spreadability (18.24–35.13 mm²), viscosity (33,260–54,420 cps), and homogeneity, ensuring stability and user compatibility. Anti-inflammatory evaluations highlight the potent inhibitory effects of FM-7, FM-8, and FM-10 on albumin denaturation, with FM-10 surpassing diclofenac. Additionally, in vitro drug release studies demonstrate FM-10’s superior release profile, indicating efficient drug delivery. The findings support the therapeutic potential of these formulations, particularly for inflammation-related disorders, and provide a foundation for further pharmaceutical development. .